Effect of Wuda granule on gastrointestinal function recovery after laparoscopic intestinal resection: a randomized–controlled trial. (16th February 2022) - Zeng, Haiping; Wang, Wei; Cao, Lixing; Wu, Yuyan; Ouyang, Wenwei; Diao, Dechang; Wan, Jin; Chen, Qicheng; Chen, Zhiqiang
Abstract: Background: Previous studies have suggested that the Wuda granule (WDG) could promote the recovery of gastrointestinal (GI) function after gynecologic abdominal surgery. This trial aimed to investigate the efficacy and safety of WDG in the rapid recovery of GI function in patients after laparoscopic intestinal resection in the setting of enhanced recovery after surgery (ERAS)-based perioperative care. Methods: We performed a randomized, double-blind, placebo-controlled pilot trial. Thirty patients who met the inclusion criteria were randomly assigned to either the WDG group or the placebo group in a 1:1 ratio. The patients received WDG or placebo twice a day in addition to ERAS-based perioperative care, starting on post-operative Day 1 until Day 3. The primary outcomes were time to first bowel movement and time to first tolerance of solid food. The secondary outcomes were time to first flatus, length of hospital stay (LOS), and post-operative ileus-related morbidity. Adverse events were also recorded. Results: There were no statistically significant differences in baseline characteristics between the two groups. The median time to first bowel movement was significantly decreased in the WDG group compared with the control group (27.6 vs 50.1 h; P  <   0.001), but the median times to first flatus (22.9 vs 25.1 h; P  >   0.05) and LOS (5.0 vs 5.0 days; P  >   0.05) were not statistically different. The occurrence rates of post-operative nausea, vomiting, abdominal distension, and abdominal pain were similar in the two groups. No adverse events occurred in any patients. Conclusions: The addition of WDG to ERAS post-operative care after laparoscopic intestinal resection can safely promote the rapid recovery of GI function.